SPECIFIC FEATURES OF ANESTHETIC SUPPORT IN THYROID SURGERY WITH NEUROMONITORING OF RECURRENT LARYNGEAL NERVES - M. A. Alekseev; V. A. Makarin; O. V. Kuleshov; A. A. Uspenskaya; A. Yu. Kulikov; Yu. N. Fedotov; A. N. Bubnov (Вестник анестезиологии и реаниматологии, 2017)
The literature review describes the specifics of anesthesia when performing surgeries on the thyroid and parathyroid glands with neuromonitoring of recurrent laryngeal nerves. This technique has been described, the rationale of its use and role of the anesthesiologist in the provision of full functioning of neuromonitoring have been investigated. The article describes the anesthesia techniques (choice of neuromuscular relaxant, hypnotic and analgesic agents), method of endotracheal tube insertion, electrode positioning, causes of potential failures and ways of their management.